Nigeria Economic Report, November 2015 - World Bank Group (World Bank, Washington, DC, 2016)
The Nigeria Economic Report (NER) is a regular publication of the World Bank. Each edition provides an overview of recent macroeconomic developments and devotes special attention to a topic of particular relevance or urgency. In this edition the macroeconomic overview is followed by both a detailed analysis of the country’s fuel subsidy and an assessment of the current state and economic potential of its natural gas sector. 2015 has been a momentous year for Nigeria. The general elections held in March brought about the first democratic transition of power from a ruling party to an opposition party, heightening expectations for meaningful political change. The new Government is taking power during a very challenging time, however, marked by a sharp decline in global oil prices and continuing violence in the country’s northeast. This creates a difficult context for realizing the new administration’s ambitious reform agenda for job creation, the power sector, oil and gas, agriculture, and public administration. Chapter two of the report analyzes the costs and benefits of Nigeria’s fuel subsidy, including their implications for low-income households. Fuel subsidy costs are expected to amount to 18 percent of government oil revenues in 2015, and this share could increase to more than 30 percent by 2018 even if oil prices remain low. There is a general consensus that increasing the supply of power in Nigeria is critical to the future development of the country. The success of the current plans to boost generation capacity will hinge on the development of the natural gas sector. Nigeria is endowed with substantial natural gas reserves, but major reforms will be necessary to attract the investment necessary to harness the potential of the natural gas sector to supply the domestic energy market. Chapter three of this report summarizes the current regulatory situation in the natural gas sector and outlines potential avenues for reform.